Analisis Pengendalian Kebisingan Melalui Pemetaan Untuk Mengurangi Paparan Populasi di Area Pelabuhan Batu Ampar Kota Batam - Ahmad Viqri; Shinta Indah; Vera Surtia Bachtiar (REACTOR: Journal of Research on Chemistry and Engineering, 2023)
Batu Ampar Port is the largest loading and unloading port of the three existing loading and unloading port facilities in Batam and the largest port for manufactured goods used by companies to supply the industrial sector in Batam. In addition to having a positive impact, the Batu Ampar port also has a negative impact in the form of a decrease in environmental quality, especially the noise level generated by activities in the Batu Ampar Port area. In this study the noise sampling process used the Svantek tool, sampling was carried out for 24 hours with a time limit of 24 intervals, then sampling was carried out for 10 minutes at each time interval. The research results obtained were that from all sampling points the highest noise was in the East Pier area of 70 – 78.5 dB(A) at 08:00 – 23:00 WIB. While the area with the lowest noise level is in the BPJS flat area of 54.7 – 73.5 dB(A) at 06:00 – 05:00 WIB. It can be concluded that many of the noise values obtained exceed the quality standards in accordance with Kepmen LH No. 48 of 1996. This was due to several factors, namely loading and uploading of very dense containers which resulted in more and more work activities. Noise elimination measures in the Batu Ampar port area are important to do considering the results of noise measurements still exceed the quality standards, Barriers are one of the technologies that can be applied to reduce noise in the Batu Ampar port, Batam, both natural and artificial barriers, so the Batu Ampar port noise problem can be solved.